2014
DOI: 10.1186/1471-2407-14-615
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic cytotoxic activity toward breast cancer cells enhanced by the combination of Antp-TPR hybrid peptide targeting Hsp90 and Hsp70-targeted peptide

Abstract: BackgroundHeat shock protein (Hsp) 90 and Hsp70 are indispensable for cell survival under conditions of stress. They bind to client proteins to assist in protein stabilization, translocation of polypeptides across the cell membrane, and recovery of proteins from aggregates in the cell. Therefore, these proteins have recently emerged as important targets in the treatment of cancer. We previously reported that the newly designed Antp-TPR hybrid peptide targeting Hsp90 induced cytotoxic activity to cancer cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The results revealed that the expression of HSP70, HSP90, anti-apoptotic Bcl-2 proteins, pro-apoptotic Bax proteins and MIFs in the two groups were significantly different. HSP70 and HSP90 are two important HSPs and one of the target proteins of HSF1, which are currently found to be highly expressed in many tumor tissues for promoting tumor development and metastasis ( 19 , 20 ). Anti-apoptotic Bcl-2 proteins and pro-apoptotic Bax proteins are the key proteins determining the fate of cells, and Bcl-2/Bax ratio variation determines the cells' tendency to apoptosis or normality ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the expression of HSP70, HSP90, anti-apoptotic Bcl-2 proteins, pro-apoptotic Bax proteins and MIFs in the two groups were significantly different. HSP70 and HSP90 are two important HSPs and one of the target proteins of HSF1, which are currently found to be highly expressed in many tumor tissues for promoting tumor development and metastasis ( 19 , 20 ). Anti-apoptotic Bcl-2 proteins and pro-apoptotic Bax proteins are the key proteins determining the fate of cells, and Bcl-2/Bax ratio variation determines the cells' tendency to apoptosis or normality ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“… 14 - 17 Therefore, targeting and potentially inhibiting HSP70 is a promising strategy in cancer therapy. 18 Rérole and coworkers have investigated a library of small peptide-aptamers and found a number of potential candidates that exhibited high affinity for HSP70, as well as enhanced chemo-sensitization. 19 Thus, these aptamers show significant potential as a therapeutic strategy for overcoming multidrug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs dysregulation in human cancer came from molecular studies characterizing the loss of chromosomal region 13q14 in human chronic lymphocytic leukemia (CLL) ( 11 ), which revealed that two miRNAs, mir-15a and mir-16-1, were clustered within this chromosomal region ( 12 ). Following the first finding, miRNA dysregulation has been reported in various cancers.…”
Section: Introductionmentioning
confidence: 99%